2016
DOI: 10.1038/srep24289
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm effect enhanced by modification of 1,2,3-triazole and palladium nanoparticles on polysulfone membranes

Abstract: Biofouling impedes the performance of membrane bioreactors. In this study, we investigated the antifouling effects of polysulfone membranes that were modified by 1,2,3-triazole and palladium (Pd) nanoparticles. The modified membranes were evaluated for antibacterial and antifouling efficacy in a monoculture species biofilm (i.e., drip flow biofilm reactor, DFR) and mixed species biofilm experiment (i.e., aerobic membrane reactor, AeMBR). 1,2,3-triazole and Pd nanoparticles inhibited growth of Pseudomonas aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…The antibacterial property of PdNPs was recently discovered and the reported data showed that PdNPs have a high potential for antimicrobial applications [31,33,46,47,[78][79][80]. As illustrated in Figure 1, the antibacterial mechanism of PdNPs included both physical and chemical modes.…”
Section: Palladium Nanoparticles For Antibacterial Therapymentioning
confidence: 96%
“…The antibacterial property of PdNPs was recently discovered and the reported data showed that PdNPs have a high potential for antimicrobial applications [31,33,46,47,[78][79][80]. As illustrated in Figure 1, the antibacterial mechanism of PdNPs included both physical and chemical modes.…”
Section: Palladium Nanoparticles For Antibacterial Therapymentioning
confidence: 96%
“…For EPS analysis, both polysaccharides and proteins concentration were measured as described in a previous study (50). Firstly, 2 mL of biofilm suspension was filtered through 0.22 µm syringe filter to quantify only the filtrate (i.e., dissolved constituents).…”
Section: Bacteriophages Isolation and Characterization Bacteriophagementioning
confidence: 99%
“…The membranes were harvested using similar protocols detailed in an earlier study. 9 The sludge in the reactor was sampled weekly for analyses. The COD in the effluent was quantified weekly.…”
Section: Reactor Configuration and Operating Conditionsmentioning
confidence: 99%
“…Examples of antifouling strategies include physical disruption of biofilm matrices using backwash, chemical wash or sonication, 8 chemical modification of membranes (e.g. coating with nanoparticles and modifying membranes with organic functional groups) 9 and biocidal control (e.g. quorum quenching and phage-based decomposition).…”
Section: Introductionmentioning
confidence: 99%